Abnormal expression of cortical cell cycle regulators underlying anxiety and depressive-like behavior in mice exposed to chronic stress - Mendes-Silva, Ana Paula; Prevot, Thomas Damien; Banasr, Mounira; Sibille, Etienne; Diniz, Breno Satler (Frontiers in Cellular Neuroscience, 2022)
Background: The cell cycle is a critical mechanism for proper cellular growth, development and viability. The p16INK4a and p21Waf1/Cip1are important regulators of the cell cycle progression in response to internal and external stimuli (e.g. stress). Accumulating evidence indicates that the prefrontal cortex (PFC) is particularly vulnerable to stress, where stress induces, among others, molecular and morphological alterations, reflecting behavioral changes. Here, we investigated if the p16INK4a and p21Waf1/Cip1 expression are associated with behavioral outcomes. Methods: PFC mRNA and protein levels of p16INK4A and p21Waf1/Cip1 of mice (6 independent groups of C57BL/6J, 8 mice/group, 50% female) exposed from 0 to 35 days of chronic restraint stress (CRS) were quantified by qPCR and Western Blot, respectively. Correlation analyses were used to investigate the associations between CKIs expression and anxiety- and depression-like behaviors. Results: Our results showed that the prefrontal cortex activated the cell cycle regulation pathways mediated by both CKIs p16INK4A and p21Waf1/Cip1 in mice exposed to CRS, with overall decreased mRNA expression and increased protein expression. Moreover, correlation analysis revealed that mRNA and protein levels are statistically significant correlated with anxiety and depressive-like behavior showing a greater effect in males than females. Conclusions: Our present study extends the existing literature providing evidence that prefrontal cortex cells respond to chronic stress exposure by overexpressing CKIs. Furthermore, our findings indicated that abnormal expression of p16INK4A and p21Waf1/Cip1 may significantly contribute to non-adaptive behavioral responses.